“…i pagt med tidens udvikling og den rivende ændring af samfundets struktur” - Reeh, Tine (Dansk Teologisk Tidsskrift, 2012)
The theologian and politician Bodil Koch was an influential player in politics regarding the Danish national church in the 20th century. During her twenty-four years as MP for the Social Democrats she made an effort to avoid an independent constitution of the Church and a separation of church and state. During her thirteen years as Minister of Ecclesiastical Affairs she worked to adjust the church to the welfare state. This article examines one of her initiatives: A commission to modernize the structure of the church. The surveys and studies from the commission introduced methods from sociology and social science into the field of church politics in Denmark. The work focused on the activities of the church and it revealed a scarce knowledge of traditional Christianity among the members as well as low Church attendance. Thus the introduction of social science in the ecclesiastical sphere reinforced public notions of a gap between the Danish national Church and the Danish population – against all intentions.